AGRESSIV VA ZO‘RAVONLIK FENOMENOLOGIYASINING PSIXOLOGIK ASOSLARI - Yusupova, Yo. (SCIENCE and SOCIETY, 2024)
This article presents a scientific explanation of the concepts of aggression and violence in psychology. It is explained that aggressive behavior is one of the forms of response to various unfavorable physical and mental life situations that cause stress, frustration, etc. Aggression is an innate characteristic of a person, which manifests itself in destructive actions or weakens in the course of education and personality development, and it is shown by the analysis of studies that it does not have the meaning of hostility.